UPDATE ON MICRONUTRIENTS IN BARIATRIC SURGERY: A COMPREHENSIVE SYSTEMATIC REVIEW - Fitriana, Ilma; Intan Permatasari, Dela (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Obesity is a major problem in the world and bariatric surgery is an effective solution for weight loss and resolving related health issues. There are three different types of bariatric surgeries. However, nutritional imbalances are a common issue after these procedures. Therefore, individuals who opt for bariatric surgery require continuous monitoring of their micronutrient levels and ongoing supplementation. This study aims to serve as a comprehensive systematic review of updates on micronutrients in bariatric surgery in the literature of the last 10 years. Methods: This review adhered to the PRISMA 2020 guidelines and analyzed English literature published between 2014 and 2024, inclusive of full-text articles. Articles such as editorials, review papers from the same journal, and those without a DOI were not included in the review. The literature was obtained from various online platforms, including PubMed, SagePub, and Science Direct. Result: Our team of researchers initially collected 3165 articles from credible sources that included PubMed, SagePub, and Science Direct. Following a rigorous three-level screening process, only six articles were found to be directly relevant to our ongoing systematic review and were then selected for further analysis through thorough full-text reading. Conclusion: Bariatric surgery, especially RYGB, can cause micronutrient deficiencies. Vitamin deficiencies (A, D) are common and iron deficiency anemia is prevalent. Zinc, copper, and selenium deficiencies can also occur. Regular supplement intake is crucial to maintain optimal micronutrient levels.